Midwifery workforce profile in Limpopo Province referral hospitals - Sam T. Ntuli; Gboyega A. Ogunbanjo (AOSIS, 2014)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE <![endif]--> Background: In sub-Saharan Africa including South Africa, maternal mortality rates remain unacceptably high due to a shortage of registered nurses with advanced midwifery diplomas. Objective: To determine the profile of registered nurses (RNs) involved in maternity care in public referral hospitals of the Limpopo Province, South Africa. Method: A cross-sectional descriptive study was conducted in all maternity units of Limpopo's public referral hospitals. The study population comprised of 210 registered nurses, who became the study sample. Data on their educational profile and work experience in midwifery was analysed using STATA version 9.0. Results: The mean age of the 210 registered nurses was 44.5 ± 9.1 years (range 21 to 62). The majority (152/210; 70%) were 40 years and older, 56% (117/210) had been working for more than 10 years, and 63/210 (30%) were due to retire within 10 years. Only 22% (46/210) had advanced midwifery diplomas, i.e. after their basic undergraduate training. Only six (2.9%) of the RNs providing maternity care in these referral hospitals were studying for advanced midwifery diplomas at the time of the study. Conclusion: This study demonstrated a shortage of registered nurses with advanced midwifery training/diplomas in referral hospitals of the Limpopo Province. This has a potentially negative effect in reducing the high maternal mortality rate in the province. <!--[if gte mso 9]> <w:LsdException Locked="false" Priority="30" SemiHidden="false" UnhideWhenUsed="false" QFormat="true"